Prosociality and health: Identification with all humanity is a replicable predictor of prosocial motivation for health behaviors - Cortes Barragan, Rodolfo; Meltzoff, Andrew N. (Frontiers in Psychology, 2023)
The acute phase of the COVID-19 pandemic has passed, but the pandemic remains a major worldwide health concern that demands continuing vigilance. Are there individual differences that predict the motivation to continue to wear masks and to create physical distance in public? Previous research conducted early in the pandemic had suggested that a particular social identity—identification with all humanity—is one underlying factor that contributes to people’s cooperation with health behavior guidelines. This highlights that the pandemic is not only an issue to be tackled with the tools of immunology or epidemiology. It also requires the tools from psychology—to measure the representations people have about themselves and others and how these representations drive values and decisions related to health. Here we report work on U.S. respondents that examined whether individuals’ level of identification with all humanity predicts their prosocial health behaviors aimed at mitigating the spread of COVID-19. In 3 convergent studies (total N = 1580), we find that identification with all humanity predicted the prosocial motivation to wear masks and to engage in physical distancing when in public without a mask. Results obtained while controlling for a host of covariates, including demographics, Big Five personality dimensions, and political ideology. We find that some people have a marked drive to care for the health of strangers, which is significantly linked to their concern for all humanity rather than being restricted to their care for their community or country. Discussion focuses on this social identification with humanity and its enduring, replicable role in predicting the motivation to engage in prosocial health behaviors. We note key implications for theories in social and developmental psychology as well as for research that may lead to practical applications for lessening the human toll of the current and future pandemics.